2008
DOI: 10.4176/080101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sympathetic Antagonists on the Antidepressant Action of Alprazolam

Abstract: Alprazolam is an anti-anxiety drug shown to be effective in the treatment of depression. In this study, the effect of sympathetic receptor antagonists on alprazolam–induced antidepressant action was studied using a mouse model of forced swimming behavioral despair. The interaction of three sympathetic receptor antagonists with benzodiazepines, which may impact the clinical use of alprazolam, was also studied. Behavioral despair was examined in six groups of albino mice. Drugs were administered intraperitoneall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In contrast to these potentially therapeutic properties of beta blockers, it has also been suggested that these drugs can promote depression-like behavior in rodents (Abel and Hannigan, 1994 ; Stone and Quartermain, 1999 ; Al-Tubuly et al, 2008 ) including in the presence of other putative antidepressants (Zhang et al, 2009 ; Gu et al, 2012 ), or under some circumstances, they have no substantial effect either alone or when co-administered with other putative antidepressants (Danysz et al, 1986 ; Evangelista et al, 1987 ; Finnegan et al, 1987 ; Teste et al, 1990 ; Beĭer, 1994 ; Detke et al, 1995 ; Pesarico et al, 2014 ; Sekio and Seki, 2015 ; Zaidi et al, 2020 ). A number of studies also suggest that the beta3 agonist amibegron (also called SR58611A) has antidepressant-like properties in rodents (Consoli et al, 2007 ; Overstreet et al, 2008 ; Stemmelin et al, 2008 , 2010 ; Tamburella et al, 2010 ), and it may achieve these effects by modulating serotonergic and noradrenergic signaling that is triggered by activation of beta3 receptors (Claustre et al, 2008 ).…”
Section: Beta Blockersmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these potentially therapeutic properties of beta blockers, it has also been suggested that these drugs can promote depression-like behavior in rodents (Abel and Hannigan, 1994 ; Stone and Quartermain, 1999 ; Al-Tubuly et al, 2008 ) including in the presence of other putative antidepressants (Zhang et al, 2009 ; Gu et al, 2012 ), or under some circumstances, they have no substantial effect either alone or when co-administered with other putative antidepressants (Danysz et al, 1986 ; Evangelista et al, 1987 ; Finnegan et al, 1987 ; Teste et al, 1990 ; Beĭer, 1994 ; Detke et al, 1995 ; Pesarico et al, 2014 ; Sekio and Seki, 2015 ; Zaidi et al, 2020 ). A number of studies also suggest that the beta3 agonist amibegron (also called SR58611A) has antidepressant-like properties in rodents (Consoli et al, 2007 ; Overstreet et al, 2008 ; Stemmelin et al, 2008 , 2010 ; Tamburella et al, 2010 ), and it may achieve these effects by modulating serotonergic and noradrenergic signaling that is triggered by activation of beta3 receptors (Claustre et al, 2008 ).…”
Section: Beta Blockersmentioning
confidence: 99%
“…Alpha1 antagonists such as prazosin and benoxathian can also exhibit antidepressant-like activity in the FST or TST (Sekio and Seki, 2015 ; Kurosawa et al, 2016 ; Wu et al, 2017 ), including potentiation of other putative antidepressants such as imipramine (Al-Tubuly et al, 2008 ). In contrast, it has also been suggested that alpha1 antagonists can promote depression-like behavior (Stone and Quartermain, 1999 ; Al-Tubuly et al, 2008 ), including in the presence of other putative antidepressants or electroconvulsive therapy (ECT; Danysz et al, 1986 ; Poncelet et al, 1987 ; Teste et al, 1990 ; Kaster et al, 2007 ; Sugimoto et al, 2011 ; Gu et al, 2012 ; Ribeiro and Pupo, 2015 ).…”
Section: Alpha1 Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation